Changes in Assessment of and Satisfaction With Discharge Preparation From the Neonatal Intensive Care Unit. (13th October 2021) - Smith, Vincent C.; Mao, Wenyang; McCormick, Marie C.
Abstract : Background: A successful transition from the neonatal intensive care unit (NICU) to home is aided by a comprehensive discharge planning program that keeps families involved and engaged with the discharge preparation process. Purpose: To compare the assessment of parental NICU discharge preparedness with parental satisfaction with the NICU discharge preparation. Methods: Families were surveyed 4 to 6 weeks after NICU discharge, and those selecting "very prepared" were considered "satisfied" with their discharge preparation. On discharge day, families were considered "prepared" for discharge based on their overall level of preparedness and their nurse's rating of them on a discharge readiness assessment tool. Results: In total, 1104 families (60%) reported being both "satisfied" and "prepared"; 293 families (16%) were "satisfied" but not "prepared"; 297 families (16%) were not "satisfied" but were "prepared"; and 134 families (7%) were neither "satisfied" nor "prepared." Compared with families that were both "satisfied" and "prepared, " families that were neither "satisfied" nor "prepared" were more likely to be raising the infant alone, of Black race, and to have sicker infants. Implications for Practice: Some families are at a higher risk and merit more consideration during NICU discharge planning. Assess the discharge readiness of all families prior to discharge. Those at an increased risk may benefit from more discharge education and training, specifically for single mothers, those with limited resources, or others considered at high risk.